Ethics and Intellectual Property Rights in Genetic Therapy - Raymond R. Tjandrawinata; Ina Heliany; Henry Soelistyo Budi (Asian Journal of Social and Humanities, 2025)
Genetic technology, particularly CRISPR-Cas9, has transformed the paradigm of treating genetic diseases by offering new hope for more effective and precise therapies. However, this advancement also presents significant ethical and intellectual property rights (IPR) challenges. This article explores the impact of patents on the development and accessibility of genetic therapy, as well as the ethical issues arising from human genetic modification, especially at the germline level. Using a qualitative analytical approach that combines literature reviews and case studies, the article examines patent disputes that have emerged in the development of CRISPR and how applied patent policies can exacerbate inequities in access to critically needed medical therapies. Furthermore, the article discusses ethical concerns regarding the misuse of genetic technology and its potential impact on future generations. In conclusion, the article proposes the need for more inclusive and balanced policies that prioritize both innovation and accessibility, as well as strict regulations to ensure the safe and ethical application of genetic technology, while considering broader social and cultural impacts.